The effect of stretching and tie layer composition on adhesion strength of multi-layered films. (July 2022) - Paul, Mou; Morris, Barry; Weinhold, Jeff; Hausmann, Karlheinz
Multilayer films are widely used in flexible packaging to provide an optimum balance of performance and cost. Orientation in the semi-solid state via tenter frame, double bubble, and machine direction orientation processes enhances barrier and mechanical properties and offers a means toward light weighting packaging structures. Interlayer adhesion of coextruded films, however, substantially decreases during the orientation as the generated new interfacial area decreases bond density and chain segments are stressed. A guideline is proposed that provides insight into how changes during orientation in chain segment penetration, entanglement, bond orientation, and density affect peel strength because of semi-solid state orientation. Examples are provided that use these insights to design novel tie resins with improved performance.